2009
DOI: 10.1007/s11144-009-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of sol–gel derived TiO2 co-doped with iron and niobium

Abstract: Titanium dioxide (TiO 2 ) photocatalysts co-doped with iron (Fe) and niobium (Nb) were synthesized using a temperature-controlled sol-gel method. The photocatalysis products were characterized and the photocatalytic activities were evaluated by the degradation of aqueous methyl orange solution. Enhanced photocatalytic activity compared to undoped TiO 2 was attributed to the cooperative effects of metal dopants, Fe and Nb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Fe:Nb co-doped and undoped TiO 2 (labeled as SG-TiO 2 ) were prepared using the temperature-controlled sol-gel process described in literature [11]. For the co-doped sample, the volume of TiO 2 precursor (titanium tetraisopropoxide) and weight of metal sources (ferric nitrate and ammonium niobium oxalate) were pre-determined to obtain a TiO 2 photocatalyst product containing 0.25 mol% Fe:Nb (1:1), labeled as Fe:Nb-TiO 2 .…”
Section: Synthesis and Characterization Of Fe And Nb Co-doped Photocamentioning
confidence: 99%
“…Fe:Nb co-doped and undoped TiO 2 (labeled as SG-TiO 2 ) were prepared using the temperature-controlled sol-gel process described in literature [11]. For the co-doped sample, the volume of TiO 2 precursor (titanium tetraisopropoxide) and weight of metal sources (ferric nitrate and ammonium niobium oxalate) were pre-determined to obtain a TiO 2 photocatalyst product containing 0.25 mol% Fe:Nb (1:1), labeled as Fe:Nb-TiO 2 .…”
Section: Synthesis and Characterization Of Fe And Nb Co-doped Photocamentioning
confidence: 99%
“…Also, ZnO doped with Cr, Mn and Fe has showed novel attention due to the strong correlation between the structural, optical, and magnetic properties [23]. Doping with various amount of Fe 3+ not only enhances electron-hole pair separation by decrease the band gap to make advantages of shifting the absorption to the visible light spectrum, but also decrease the average grain size [24,25]. As reported in the literature, the presence of more than one valence states on transition metal ion suggests that polaronic conduction is attributed to a hopping mechanism of electrons from low valence state to the high valance one [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, concentration and distribution of dopant ions in TiO 2 are factors that must be considered for a good photocatalytic performance [13]. The incorporation of two types of cations into TiO2 lattice and its photocatalytic performance has been reported in several studies [14,15]. Estrellan et al [14] reported that when the TiO2 is co-doped with iron and niobium, the photocatalytic efficiency is improved due to synergistic actions between the doping species, which favor the e−/h+ generation and reduce the recombination rate.…”
mentioning
confidence: 99%